Information management and industrial harmony for organisational development in Nigeria (2020)
Harmony remains an inevitable aspect both in human societies and Industries. Where there are unrests and chaos, meaningful progress and productivity will be negatively affected. In order to maintain peaceful coexistence there is the need for an effective communication System within any Organization. Good and positive management of Information in both horizontal and vertical directions will no doubt impact on peaceful coexistence among all relevant stakeholders - management, workers and labour leaders. The recurrence of industrial conflicts in the Nigerian labour industry has in so many ways hampered the-economic development of the nation resulting into huge losses due to persistent disharmony in the labour sector. This paper examines how management of Information could help in achieving industrial harmony to promote economic development in Nigeria. The paper concludes by suggesting some strategies on the utilization of Information for the promotion of industrial harmony